The effect of video games towards children's communication / Fatimah Yazmin Yahaya ... [et al.] - Yahaya, Fatimah Yazmin; Mohd Azni, Zuliani; Hassan, Mohd Sufiean; Suhaini, .; Shaiful Badrin, Fisha Dayana; Mohd Zulfikar, Sara Nur’ain; Sahri, Muhammad Heelal (Faculty of Information Management, 2023)
The significant popularity of video games and their ability to make players enjoy the participation of players to play video games rapidly led to the video game industry transitioning from the entertainment side to being involved in most other aspects of life. This study researches how video games affect children's communication. The method of this paper is qualitative, which analyses content from previous studies that conduct surveys and interviews towards children and their parents regarding the children's communication skills, behaviour pro-social skills and speech development. This study aims to explore if video games positively or negatively affect children aged 7 to 12 years in terms of their online and offline social skills, problem behaviour, pro-social behaviour and speech development. The finding of this study is that video games affect children's communication more negatively toward their social skills, problem behaviour, and pro-social behaviour.